1976
DOI: 10.1002/j.2050-0416.1976.tb03745.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Yeast Esterase

Abstract: An esterase (carboxylic acid hydrolase EC 3 1.1.1.) has been prepared from Saccharomyces cerevisiae. This esterase is active at pH 4 4 and, though it is unstable in solution, it can be main tained in an active form either by lyophilization or by coupling to an affinity gel. At pH 4 4, yeast esterase can hydrolyse between 20 and 40% of the esters commonly present in beer, and it is capable of synthesizing ethyl acetate from ethanol and acetic acid in a simple buffered solution without the provision of a co-fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…As esterases are responsible for the breakdown of esters, it is clear that their activity may affect the concentration of certain volatile esters. In S. cerevisiae, for example, it has been shown that the balance between ester-synthesizing enzymes and esterases, such as Iah1p (also known as Est2p), is important for the net rate of ester accumulation (27)(28)(29)(30) (59,60,61,62,70). This indicates that esterases may also play a role in the formation of certain esters (42,62,70).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As esterases are responsible for the breakdown of esters, it is clear that their activity may affect the concentration of certain volatile esters. In S. cerevisiae, for example, it has been shown that the balance between ester-synthesizing enzymes and esterases, such as Iah1p (also known as Est2p), is important for the net rate of ester accumulation (27)(28)(29)(30) (59,60,61,62,70). This indicates that esterases may also play a role in the formation of certain esters (42,62,70).…”
Section: Discussionmentioning
confidence: 99%
“…In S. cerevisiae, for example, it has been shown that the balance between ester-synthesizing enzymes and esterases, such as Iah1p (also known as Est2p), is important for the net rate of ester accumulation (27)(28)(29)(30) (59,60,61,62,70). This indicates that esterases may also play a role in the formation of certain esters (42,62,70). In Acetobacter pasteurianus, for example, deletion of the esterase-encoding gene est1 causes the abolishment of ethyl acetate and isoamyl acetate production (15,36,37,50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their sensory threshold is very low, and thus they have a strong influence on the aroma of alcoholic beverages, giving characteristic flavours to, for example, wine 25 , beer 23 and sake 7 . Therefore, the study of enzyme activities, affecting the ester content and spectrum, is of primary importance in elucidating the mechanisms leading to the formation of the aroma profile of a fermented beverage such as wine.…”
Section: -2863(9'8-32mentioning
confidence: 99%
“…Esterases are expressed in yeast strains used for alcoholic beverage production and their involvement in affecting the aroma of such beverages has been the subject of several studies. By regulating the equilibrium between esters and free acids, esterases might determine ester synthesis 3,12,20,23,25 , but seem to be mainly involved in their breakdown 6,8,12 . For example, isoamyl acetate, which is thought to be synthesized from isoamyl alcohol and acetyl CoA by yeast alcohol acetyltransferase, is hydrolyzed by yeast esterases in sake mash 7,8 thus affecting the flavour quality of this beverage.…”
Section: -2863(9'8-32mentioning
confidence: 99%